Achieving Sustainable Development Goals from a Water Perspective - Bhaduri, Anik; Bogardi, Janos; Siddiqi, Afreen; Voigt, Holm; Vörösmarty, Charles; Pahl-Wostl, Claudia; Bunn, Stuart E.; Shrivastava, Paul; Lawford, Richard; Foster, Stephen; Kremer, Hartwig; Renaud, Fabrice G.; et al. (Frontiers in Environmental Science, 2016)
Efforts to meet human water needs only at local scales may cause negative environmental externality and stress on the water system at regional and global scales. Hence, assessing SDG targets requires a broad and in-depth knowledge of the global to local dynamics of water availability and use. Further, Interconnection and trade-offs between different SDG targets may lead to sub-optimal or even adverse outcome if the set of actions are not properly pre-designed considering such interlinkages. Thus scientific research and evidence have a role to play in facilitating the implementation of SDGs through assessments and policy engagement from global to local scales. The paper addresses some of these challenges related to implementation and monitoring the targets of the Sustainable Development Goals from a water perspective, based on the key findings of a conference organised in 2015 with the focus on three essential aspects of SDGs- indicators, interlinkages and implementation. The paper discusses that indicators should not be too simple but ultimately deliver sustainability measures. The paper finds that remote sensing and earth observation technologies can play a key role in supporting the monitoring of water targets. It also recognises that implementing SDGs is a societal process of development, and there is need to link how SDGs relate to public benefits and communicate this to the broader public.